[The North African plague and Charles Nicolle's theory of infectious diseases]. - (:unkn) unknown (My University, 2010)
Many infectious diseases were described in North Africa in 18th-19th centuries by European travellers. Most of them were allegedly imported by new migrant populations coming from sub-Saharan, European or Middle East countries. Plague outbreaks have been described since the Black Death as diseases of the Mediterranean harbours. Charles Nicolle and his collaborators at the Pasteur Institute were witnesses to the extinction of plague and typhus fever in Tunisia. Both could be considered as endemo-epidemic diseases propagated by ancient nomad communities for centuries. Typhus was exported to other countries; plague was imported by Mediterranean travellers but also hid in unknown wild-animal reservoirs. The role of the bite of a rat's flea was not confirmed and the pneumonic form might have prevailed in the medieval North African cities. Association between plague, typhus, flu and other causes of immune deficiencies could explain the high morbidity and mortality caused by plague in the past. The authors comment the local history of plague at the light of the evolutionary laws of infectious disease proposed by Charles Nicolle in 1930.
Keywords: African Research